Analisis Isi Komentar pada Media Sosial Instagram @HABISNONTON - Agung Parasetia; Andini Putri Lstari; Elok Anjelika; Sitti Wardaniah; Yohanes Ari Kuncuroyakti (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
This research is inspired by the extraordinary success of the domestic animated film titled Jumbo, which managed to set a new record and trigger a wave of overwhelmingly positive sentiment responses on the Instagram social media platform. Its main focus is to provide a deep qualitative interpretation of audience sentiment data that was previously collected and quantitatively evaluated by Prasetia (2025) from 764 original comments, which were then filtered down to 221 samples. The approach applied involves secondary data analysis by reviewing the frequency of Prasetia's data through the lens of social identity theory and collective efficacy theory. The results of the analysis reveal that the prevalence of positive sentiment at 68.7% does not merely reflect a simple evaluation of the film but also serves as a fundamental expression of shared pride and in-group preference. Expressions of support that emphasize appreciation for the achievement and national pride over the work of local creators act as a tool for strengthening social bonds, reinforcing the national identity linked to achievements in the film sector while also demonstrating the audience's collective belief in the potential of the domestic animation industry (mastery experience). Practically, the recommendation for local film promotion strategies is to highlight narratives about shared accomplishment and national pride to build audience loyalty and continuous interaction in the digital environment.